THE EASE OF DOING BUSINESS IN INDONESIA - Adsina Fibra (Journal of Business Strategy and Execution, 2018)
The ease of doing business (EOB) is one of the indicators which attract foreign investors do business in Indonesia. Indonesia’s ease of doing business has improved from time to time but still left behind compare to other Asian countries. The current research addresses research questions; what are the business reforms which have been done by Indonesian Government in a last decade to promote the ease of doing business, what are the areas need to be improved, and how the ease of doing business gives advantages to this developing nation.  This study contributes to reveal the implementation of EOB policy in Indonesia; enrich EOB policy literature; and suggest recommendations for EOB improvement.